Biocompatible and photoluminescent keratin/poly(vinyl alcohol)/carbon quantum dot nanofiber: A novel multipurpose electrospun mat - Lee, Chohye; Pant, Bishweshwar; Alam, Al-Mahmnur; An, Taehee; Chung, Hea-Jong; Hong, Seong-Tshool; Park, Soo-Jin; Park, Mira; Kim, Hak-Yong (Macromolecular research, 2016)
Carbon quantum dots (C-dots) triggered photoluminescent keratin/poly(vinyl alcohol) (PVA)/C-dots nanofibers (NFs) with optical transparency and biocompatibility were prepared by an electrospinning process. The synthesized NFs were characterized by field-emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM), Fourier transform infrared spectroscopy (FTIR), ultraviolet-visible spectroscopy, and spectrofluorometer. C-dots are capable of emitting excitation dependent photoluminescence (PL) emission spectra at room temperature and are nontoxic at reasonably high concentrations. Optically transparent keratin/PVA/C-dots NFs were found to exhibit excitation dependent PL emission at the wavelengths of 488, 535, and 625 nm during excitation at the wavelengths of 360, 480, and 545 nm, respectively, similar to the C-dots. In vitro cytotoxicity tests against NIH-3T3 cell lines revealed a good biocompatible nature of keratin/PVA/C-dots. The results indicated that the fabricated composite NFs mat not only exhibited a well preserved quantum confinement effect of the C-dots along with its transparency but also showed biocompatibility in the living cell environment.